Experiencing mobbing at workplace facing psychological gender and occupational burnout = Doświadczanie mobbingu w pracy a płeć psychologiczna i wypalenie zawodowe - Góralewska-Słońska, Anna Maria (Zielona Góra: Faculty of Economics and Management Press)
The problem of mobbing in the work environment is significant, there are many factors determining mobbing, and its negative effects affect both the employees of the organization and their social environment as well as the work process. The aim of this study is to determine the relationship of experiencing mobbing with psychological gender dimensions and occupational burnout.
Keywords: mobbing; wypalenie zawodowe; płeć psychologiczna; occupational burnout; psychological gender